Shifts in xylanases and the microbial community associated with xylan biodegradation during treatment with rumen fluid. Issue 6 (28th December 2021) - Takizawa, Shuhei; Asano, Ryoki; Fukuda, Yasuhiro; Baba, Yasunori; Tada, Chika; Nakai, Yutaka
Summary: Treatment with rumen fluid improves methane production from non‐degradable lignocellulosic biomass during subsequent methane fermentation; however, the kinetics of xylanases during treatment with rumen fluid remain unclear. This study aimed to identify key xylanases contributing to xylan degradation and their individual activities during xylan treatment with bovine rumen microorganisms. Xylan was treated with bovine rumen fluid at 37°C for 48 h under anaerobic conditions. Total solids were degraded into volatile fatty acids and gases during the first 24 h. Zymography showed that xylanases of 24, 34, 85, 180, and 200 kDa were highly active during the first 24 h. Therefore, these xylanases are considered to be crucial for xylan degradation during treatment with rumen fluid. Metagenomic analysis revealed that the rumen microbial community's structure and metabolic function temporally shifted during xylan biodegradation. Although statistical analyses did not reveal significantly positive correlations between xylanase activities and known xylanolytic bacterial genera, they positively correlated with protozoal (e.g., Entodinium, Diploplastron, and Eudiplodinium ) and fungal (e.g., Neocallimastix, Orpinomyces, and Olpidium ) genera and unclassified bacteria. Our findings suggest that rumen protozoa, fungi, and unclassified bacteria are associated with key xylanase activities, accelerating xylan biodegradation into volatile fatty acids and gases, during treatment of lignocellulosic biomass with rumen fluid. Abstract : This study aimed to identify key xylanases contributing to xylan degradation and their individual activities during xylan treatment with bovine rumen microorganisms. Zymography and metagenomic analysis showed that xylanases of 24, 34, 85, 180, and 200 kDa were highly active during the first 24 h and correlated to several unclassified bacteria, fungi, and protozoa. Our findings suggest that rumen protozoa, fungi, and unclassified bacteria are associated with key xylanase activities, accelerating xylan biodegradation into volatile fatty acids and gases, during treatment of lignocellulosic biomass with rumen fluid.